Edukasi Hukum sebagai Upaya Pencegahan Pernikahan Dini di Kelurahan Curahgrinting, Kota Probolinggo - Ahmad Syaifuddin Romli; Ana Billah; Ah. Fathan Azhari; Qikeq Dwi Safitriningrum (Sejahtera: Pengabdian Kepada Masyarakat, 2026)
Early marriage remains a social problem, resulting in violations of children's rights, poor educational quality, and health and social risks within families. Although the minimum age for marriage is regulated by Law Number 16 of 2019, the practice of underage marriage is still found in various regions, including Curahgrinting Village, Probolinggo City. This community service activity aims to increase public understanding and legal awareness as an effort to prevent early marriage. The method used is an educational and participatory approach through legal outreach, interactive discussions, and Q&A sessions involving adolescents, parents, and community leaders. The activity stages included preparation, implementation, and evaluation, using pre- and post-test instruments to measure participants' understanding. The results of the activity indicate an increase in public knowledge and legal awareness regarding the minimum age for marriage and the legal and social impacts of early marriage. Furthermore, participants demonstrated a change in attitudes toward preventing early marriage. This activity demonstrates that legal education can be an effective and sustainable preventive measure in supporting the protection of children's rights and strengthening public legal awareness. Keywords: legal education; early marriage; community service; child protection